2007
DOI: 10.1590/s0101-31222007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Recobrimento de sementes de soja com micronutrientes, fungicida e polímero

Abstract: RESUMO -A técnica do recobrimento de sementes vem sendo utilizada com a finalidade de incorporar produtos fitossanitários, hormônios, micronutrientes, agentes biológicos e polímeros que propiciem um melhor desempenho de sementes e plântulas. O objetivo principal deste trabalho foi avaliar o efeito do recobrimento das sementes de soja cv. BRS 153 na qualidade das sementes e no desempenho das plântulas. O revestimento foi realizado com três doses de micronutrientes (CoMoB): 1, 2 e 4mL por quilo de sementes; um f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 2 publications
1
16
0
18
Order By: Relevance
“…It should be emphasized, however, that by increasing the fixation of the active products, there may be a toxic effect of products incorporated in these seeds, reducing the germination. Bays et al (2007), evaluating the physiological quality of soybean seeds after fungicide application, micronutrients (CoMoB) and covering with commercial polymer, observed that the highest dose of the micronutrient (4 mL.kg -1 of seeds) is phytotoxic when seeds are coated with fungicide and polymer. Regarding the effect of drying rates in eggplant seeds, it was observed by the results of the emergence (Table 1B and Figure 2), emergence speed index (Table 1C and Figure 3) and germination speed index (Table 1D and Figure 4) tests that in the seeds dried quickly there was the induction of secondary dormancy caused by their exposure to elevated temperatures, and that was overcome after three months of storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized, however, that by increasing the fixation of the active products, there may be a toxic effect of products incorporated in these seeds, reducing the germination. Bays et al (2007), evaluating the physiological quality of soybean seeds after fungicide application, micronutrients (CoMoB) and covering with commercial polymer, observed that the highest dose of the micronutrient (4 mL.kg -1 of seeds) is phytotoxic when seeds are coated with fungicide and polymer. Regarding the effect of drying rates in eggplant seeds, it was observed by the results of the emergence (Table 1B and Figure 2), emergence speed index (Table 1C and Figure 3) and germination speed index (Table 1D and Figure 4) tests that in the seeds dried quickly there was the induction of secondary dormancy caused by their exposure to elevated temperatures, and that was overcome after three months of storage.…”
Section: Resultsmentioning
confidence: 99%
“…However, concerns about the chemicals used allowed the incorporation of a new technique in agronomy that has been widely used by the vegetable seed industry (Medeiros et al, 2006): film coating. This technology is designed primarily to enable the incorporation of other materials such as fungicides, growth regulators and micronutrients (Oliveira et al, 2006), reduce human exposure to toxic chemicals added to the seeds (Taylor et al, 1998), allow easy identification of treated seeds (Ni and Biddle, 2001), contribute for the proper amount of active ingredients to be applied is adhered to the surface of the seeds guaranteeing their performance (Kunkur et al, 2007), in addition to providing seeds with good appearance, color and adhesion (Bays et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, para as grandes culturas, o recobrimento de sementes ainda é considerado uma nova tecnologia, pois faltam muitas informações técnico-científicas (Bays et al, 2007). A agregação de valor às sementes, utilizando métodos e tecnologias de produção como o recobrimento de sementes, é uma exigência de um mercado cada vez mais competitivo (Medeiros et al, 2004).…”
Section: Introductionunclassified
“…Contudo, vencida a barreira, as plântulas se igualam na velocidade de crescimento, formando mudas uniformes em massa fresca e seca, tanto em condições de laboratório quanto em viveiros de mudas. Bays et al (2007) observaram que o recobrimento de sementes de soja com polímero não afetou a qualidade fisiológica das sementes. Binneck et al (1999), estudando o efeito do recobrimento das sementes sobre a germinação e a emergência de sementes de trevo-branco, concluíram que com o uso de sementes recobertas, podem-se conseguir populações com altas taxas de germinação e emergência de plântulas.…”
Section: Introductionunclassified
“…According to Bays et al (2007), the primary requirement of an increasingly competitive market is to add value to the seeds, using production methods and technologies such as seed treatment. Currently, treatment is used to incorporate materials such as fungicides, micronutrients, pesticides, plant hormones and polymers which improve the performance of seeds and seedlings and even later stages of culture.…”
Section: Introductionmentioning
confidence: 99%